Evaluating the role of video in supporting reflection beyond INSET. (June 2020) - Mann, Steve; Crichton, Ross; Edmett, Adam
Abstract: This article considers the impact of a video-based initiative aimed at sustaining engagement, reflection and impact beyond a three-week INSET (in-service teacher education and training) programme. Teachers worked with mentors on a one to one basis in a process of reflecting on their own videos and clips from other teachers. The study uses interviews, recordings and transcripts of video-based talk to evaluate the design of this video-led mentor CPD (continuing professional development) intervention and to evaluate the nature of video-based reflection in this process. The analysis focused on four themes that emerged as significant in the analysis of recordings and project documents. Not surprisingly we found that reflection was orientated to INSET ('bootcamp') content although videos were sometimes sources of resistance to this content. Interactions varied based on a number of factors related to the mentor role and video type. Our findings confirmed previous studies regarding video length and type and relationship to reflection. We also found that language choice (Thai/English) was significant and that teachers may prefer to reflect in L1. We provide suggestions for how a video-based CDP intervention might help to promote reflection in teachers as well as recommendations for other educators considering video-based alternatives.